Foreign exchange operation and performance: an evaluation of Bank Asia Ltd. - Alam, Humyra Sharmind (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.